2010
DOI: 10.1007/s12022-010-9118-7
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Saccharomyces cerevisiae Antibodies are Frequent in Type 1 Diabetes

Abstract: Anti-Saccharomyces cerevisiae antibodies (ASCA) have been described in many autoimmune diseases in which there is an increased intestinal permeability. Also in type 1 diabetes (T1D), there is an increased intestinal permeability. Since no data are available about ASCA in T1D, we evaluated, retrospectively, the frequency of ASCA in this disease. ASCA, IgG, and IgA, were determined by ELISA in sera of 224 T1D patients in which coeliac disease has been excluded and 157 healthy control group. The frequency of ASCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…Information regarding certain autoimmune conditions was also lacking. In the present study, the 95% CI for the proportion of IgG positive samples ranged between 16% and 30%, which is comparable to the frequency of IgG positivity found in diseases of autoimmune origin, such as type 1 diabetes mellitus [27], systemic lupus erythematosus [28] and microscopic colitis [29], but lower than in Crohn’s disease [30]. No significant association was however detected between ASCA and disorders such as hypothyroidism or diabetes (the majority of the diabetic patients had type II diabetes).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Information regarding certain autoimmune conditions was also lacking. In the present study, the 95% CI for the proportion of IgG positive samples ranged between 16% and 30%, which is comparable to the frequency of IgG positivity found in diseases of autoimmune origin, such as type 1 diabetes mellitus [27], systemic lupus erythematosus [28] and microscopic colitis [29], but lower than in Crohn’s disease [30]. No significant association was however detected between ASCA and disorders such as hypothyroidism or diabetes (the majority of the diabetic patients had type II diabetes).…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, high concentrations of ASCA have been found in Crohn’s disease [23, 24] and other diseases associated with increased gut permeability, such as celiac disease and type 1 diabetes mellitus [2527]. A “leaky gut”, with increased translocation of Saccharomyces cerevisiae (or related antigens) could thus be one potential explanation for the increased ASCA IgG concentrations and their association with CRP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. cerevisiae could be considered as an environment factor to many autoimmune diseases. Indeed, we demonstrated a high frequency of anti-S. cerevisiae antibodies in many autoimmune diseases (8,18,(29)(30)(31).…”
Section: Discussionmentioning
confidence: 87%
“…It has also been shown that ASCA had a high predictive value for inflammatory bowel disease (5). Additionally, elevated levels of ASCA had been found in patients with Behcet's disease (6), spondyloarthritis (7), coeliac disease (8,9), intestinal tuberculosis (10), primary biliary cirrhosis (11,12), autoimmune hepatitis (13), type 1 diabetes (14), and autoimmune thyroid disease (15,16).…”
Section: Introductionmentioning
confidence: 99%